Dynamics and chemistry of vortex remnants in late Arctic spring 1997 and 2000: Simulations with the Chemical Lagrangian Model of the Stratosphere (CLaMS) - Konopka, P.; Grooss, J.-U.; Bausch, S.; Müller, R.; Mckenna, D. S.; Morgenstern, O.; Orsolini, Y. (HAL CCSD, 2003)
International audience High resolution simulations of the chemical composition of the Arctic stratosphere during late spring 1997 and 2000 have been conducted with the Chemical Lagrangian Model of the Stratosphere (CLaMS). The simulations were performed for the entire northern hemisphere on two isentropic levels 450 K (~18 km) and 585 K (~24 km). The spatial distribution and the lifetime of the vortex remnants formed after the vortex breakup in May 1997 show a completely different behavior above and below 20 km. Above 20 km, vortex remnants effectively propagate southward (up to 40° N) and are "frozen'' in the summer circulation without significant mixing. Below 20 km the southward propagation of the remnants is bounded by the subtropical jet near 55° N. Their lifetime is shorter by a factor of 2 than above 20 km, owing to significant stirring below this altitude. The behavior of vortex remnants formed in March 2000 is similar but, due to an earlier vortex breakup, dominated until mid of May by westerly winds, even above 20 km. Vortex remnants formed in May 1997 are characterized by large mixing ratios of HCl indicating a negligible contribution of the halogen-induced ozone loss. In contrast, mid-latitude ozone loss in late boreal spring 2000 is dominated by an irreversible transport of the ozone-depleted polar air masses (dilution) and, until mid of April, by halogen-induced ozone destruction within the vortex remnants. By varying the effective diffusivity of CLaMS, the impact of mixing on the formation of ClONO 2 and ozone depletion is considered. In particular, the photochemical decomposition of HNO 3 and not mixing with NO x -rich mid-latitude air is the main source of NO x within the vortex remnants in March and April 2000. Ozone depletion in the remnants is driven by ClO x photolytically formed from ClONO 2 and can be properly resolved for CLaMS spatial resolution better then 100\,km. At 450 K, ozone loss in the vortex remnants contributes by ~2% to the ozone deficit poleward of 30° N.